Oxylipins as therapeutic indicators of herbal medicines in cardiovascular diseases: a review - Li, Mengqi; He, Min; Sun, Mengmeng; Li, Yongping; Li, Mengyuan; Jiang, Xiaobo; Wang, Yanxin; Wang, Hongfeng (Frontiers in Pharmacology, 2024)
Globally, cardiovascular diseases (CVDs) remain the leading cause of death, and their prevention and treatment continue to face major challenges. Oxylipins, as novel circulating markers of cardiovascular disease, are crucial mediators linking cardiovascular risk factors such as inflammation and platelet activation, and they play an important role in unraveling cardiovascular pathogenesis and therapeutic mechanisms. Chinese herbal medicine plays an important role in the adjuvant treatment of cardiovascular diseases, which has predominantly focused on the key pathways of classic lipids, inflammation, and oxidative stress to elucidate the therapeutic mechanisms of cardiovascular diseases. However,The regulatory effect of traditional Chinese medicine on oxylipins in cardiovascular diseases remains largely unknown. With the increasing number of recent reports on the regulation of oxylipins by Chinese herbal medicine in cardiovascular diseases, it is necessary to comprehensively elucidate the regulatory role of Chinese herbal medicine in cardiovascular diseases from the perspective of oxylipins. This approach not only benefits further research on the therapeutic targets of Chinese herbal medicine, but also brings new perspectives to the treatment of cardiovascular diseases.